Hotel Wisata Kulisusu Kabupaten Buton Utara Dengan Pendekatan Arsitektur Modern - Hasmariska, Nia; Ahyarki Abidin, Afri; Al-Mustagfir Syah, Andi; Nahdatunnisa, Nahdatunnisa (Architectura : Journal of Architecture and Planning, 2025)
The development of the tourism sector in North Buton Regency, especially in Kulisusu District, requires adequate infrastructure support, one of which is a representative accommodation facility. The design of this tourist hotel aims to provide lodging facilities that are comfortable, functional, and able to increase the attractiveness of regional tourism. A modern architectural approach is used to display the impression of a building that is simple, efficient, and in accordance with the needs of today's society without ignoring the context of the tropical environment and local potential. The design is designed with attention to aspects of open space, natural lighting, good air circulation, and integration with the surrounding landscape. It is hoped that the hotel will not only serve as a place to stay overnight, but also become an icon of modern architecture that supports economic growth and tourism in the North Buton region.